2012
DOI: 10.3945/ajcn.112.034645
|View full text |Cite
|
Sign up to set email alerts
|

The role of lycopene and its derivatives in the regulation of transcription systems: implications for cancer prevention

Abstract: Evidence from epidemiologic studies has suggested that carotenoids, and lycopene in particular, decrease the risk of cancer: however, not all studies support this view. To gain insight into the molecular mechanisms whereby lycopene and other carotenoids may exert their chemoprotective effects, we and others performed a series of studies that used a large panel of cancer cell lines of different lineages and animal models of human cancer. In this review we address some of the mechanisms proposed for the cancer-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…This question is pertinent not only with respect to the NFkB system but also to several additional cellular processes found to be modulated by oxidized carotenoid derivatives [42,73]. As noted in the Introduction, in vitro oxidation of carotenoids leads to the formation of mono and dialdehyde products called apocarotenals and diapocarotene-dials, respectively [41].…”
Section: Discussionmentioning
confidence: 97%
“…This question is pertinent not only with respect to the NFkB system but also to several additional cellular processes found to be modulated by oxidized carotenoid derivatives [42,73]. As noted in the Introduction, in vitro oxidation of carotenoids leads to the formation of mono and dialdehyde products called apocarotenals and diapocarotene-dials, respectively [41].…”
Section: Discussionmentioning
confidence: 97%
“…Laboratory studies provide evidence that tomato and lycopene may suppress oxidative damage, modulate intracellular signaling resulting in reduced proliferation, and enhance sensitivity to apoptosis, among other mechanisms (6). Some evidence suggests that tomato or lycopene intake may modulate testosterone production, serum concentrations, and metabolism, and may impact gene expression in human prostate cancer cells, normal rat prostate, and established prostate cancer xenografts (7-10). However, whether lycopene and/or other tomato phytochemicals inhibit prostate cancer by targeting androgen signaling and metabolism in early stages of prostate carcinogenesis has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The capsaicinoids in the paprika extract have antioxidant effects (COSTA et al, 2010) and reduces the plasmatic cholesterol levels and the formation of atheromatous plaque in human being (HUANG et al, 2014). Several reports revised the safety of lutein for adults (JECFA, 2006;SHAO & HATHCOCK, 2006). A study concluded that 200 mcg/L lutein in formulations for babies is safe (EFSA, 2008).…”
Section: Introductionmentioning
confidence: 99%